Molecular biomineralization aquatic organisms forming extraordinary materials - Müller, Werner E.G (Progress in Molecular and Subcellular Biology, 2011)
The concept of 'biomineralization' signifies mineralization processes that take place in close association with organic molecules or matrices. The awareness that mineral formation can be guided by organic molecules notably contributed to the understanding of the formation of the inorganic skeletons of living organisms. Modern electron microscopic and spectroscopic analyses have successfully demonstrated the participation of biological systems in several mineralization processes, and prominent examples include the formation of bio-silica in diatoms and sponges. This insight has already made the application of recombinant technology for the production of valuable inorganic polymers, such as bio-silica, possible. This polymer can be formed by silicatein under conditions that cannot be matched by chemical means. Similarly, the efforts described in this book have elucidated that certain organisms, bacteria in deep-sea polymetallic nodules and coccoliths in seamount crusts, are involved in the deposition of marine minerals. Strategies have already been developed to utilize such microorganisms for the biosynthesis and bioleaching of marine deposits. Moreover, studies reveal that bio-polymers enhance the hydroxyapatite formation of bone-forming cells and alter the expression of important regulators of bone resorption, suggesting a potential for bone regeneration and treatment / prevention of osteoporosis.